Dominance of Cry1F resistance in Spodoptera frugiperda (Lepidoptera: Noctuidae) on TC1507 Bt maize in Brazil. Issue 5 (7th August 2015) - Farias, Juliano R; Andow, David A; Horikoshi, Renato J; Sorgatto, Rodrigo J; Santos, Antonio C dos; Omoto, Celso
Abstract: BACKGROUND: Dominance of resistance has been one of the major parameters affecting the rate of evolution of resistance to Bt crops. High dose is the capacity of Bt crops to kill heterozygous insects and has been an essential component of the most successful strategy to manage resistance to these crops. Experiments were conducted to evaluate directly and indirectly whether the TC1507 event is high dose to Spodoptera frugiperda (JE Smith). RESULTS: About 8% of heterozygote neonate larvae were able to survive, complete larval development and emerge as normal adults on TC1507 leaves, while susceptible larvae could not survive for 5 days. The estimated dominance of resistance was 0.15 ± 0.09 and significantly higher than zero; therefore, the resistance to Cry1F expressed in TC1507 was not completely recessive. A 25‐fold dilution of TC1507 maize leaf tissue in an artificial diet was able to cause a maximum mortality of only 37%, with growth inhibition of 82% at 7 days after larval infestation. CONCLUSION: Resistance to Cry1F in TC1507 maize is incompletely recessive in S. frugiperda . TC1507 maize is not high dose for S. frugiperda . Additional or alternative resistance management strategies, such as the replacement of single‐trait Bt maize with pyramided Bt maize, which produces multiple proteins targeting the same insect pests, should be implemented wherever this technology is in use and S. frugiperda is the major pest. © 2015 Society of Chemical Industry